Integrasi Penjadwalan Produksi dan Preventive Maintenance untuk Meminimasi Makespan dengan Menggunakan Metode Heijunka dan Batch – Backward Scheduling (Studi Kasus PT. BMC) - Sumiharni Batubara; Enrico Azcauda Nainggolan (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
PT BMC industry which produces automotive components. The problem, in the Brake Assembly Assembly Line, is that high engine downtime is caused by engine failure, resulting in production scheduling not going according to plan. The Drum Assembly Brake Line consists of BD III lines, producing Brake Drum and HUB III lines, producing Hubs. This study aims to determine the smallest and the same makespan value, for the BD III and HUB III lines using the integration of the Heijunka method and Batch Backward Scheduling with Preventive Maintenance (PM) Data processing begins by determining the sequence of jobs and completion time with Heijunka and Batch-Backward Scheduling method. Next, determine the MTTF and MTTR parameters to determine the optimal inspection interval and average repair time. In the last step, the scheduling results are integrated with the inspection and repair intervals if needed, to get the makespan value. The calculation results show that the optimal inspection interval and MTTR for the BD III line is 94 hours and 1.7 hours while the HUB III line is 116 hours with 1.2 hours. After integration of the Heijunka-PM method, the makespan is 511.8 hours and 510.3 hours for the BD III and HUB III lines. The integration of the Batch-Backward scheduling-PM method produces makespan of 538.8 hours and 540 hours for the BD III and HUB III lines. Based on the smallest makespan criteria, scheduling integration is chosen, using the Heijunka-PM method.